Toponymie littorale aux îles Marquises, Fenua ‘Enata/Henua ‘Enana, Polynésie orientale (Polynésie française) - Pierre Ottino-Garanger; Marie-Noëlle Ottino-Garanger (Revue d'ethnoécologie)
Toponymy is one of the wealth of any cultural heritage and expresses knowledge that is passed on from one generation to another and relate to the entire territory. Each peak, reef, cliff, bay, cove or shoal illustrates the perfect identification of a place, the use and various know-hows and activities associated with it. They give us information on natural features, important characteristics or events, and sometimes tell a story, refer to ancient times, deities and local heroes, often pan-Polynesian. They mostly demonstrate the importance of the coast and sea in the Marquesan culture, where fishing and fishermen play an essential part, still to this day, and even more in ancient times. Toponymy is very rich there, quite well preserved, but necessarily geolocated as are still, in some way, inhabitants who live in islands and valleys that are still separated despite the evolution of the means of communication. Hence the importance of going in the field, in each inhabited place of the 6 islands, which is about thirty valleys, more or less easily accessible, to gather as much toponymy as possible with the only people who know these places. Sharing knowledge is necessary as well as collaboration between protagonists in order to stimulate and mobilize memory so as to rediscover names, locations and uses. These collections result in a surprisingly rich reproduction. Maps favor people’s involvement in the acquisition, sharing, confirming and reproduction processes. Spontaneous participation allows us to gather several hundreds of toponyms. There is still a lot to do to translate the underlying cultural essence of these places’ names.